Physical training for the mass of students - Sweet, K. Elizabeth (My University, 1904)
Introduction: The results of physical training are many. There is a direct relationship between the physical condition and intellectual capacity, the latter varying directly as the former. State Supt.A.B.Poland, of New Jersey says in his article on the "Scientific Value of Physical Culture," that there is a basis for the cry against pushing the intellectual training too far for the good of society and of the individual. He says that this warrants the interest taken at present in physical culture. He says it is an absolute necessity for the well being of not only the present generation but of generations to come. There must be an equal development of mind and body. He says that to be effective physical training must be organized,supervised,and controlled,as effectively as intellectual education. One author has said, "Physical culture adds dignity and strength of character in proportion as dignity of attitude becomes habitual and is reflex in its action." It gives self-possession in the place of self consciousness. Only when we give equal attention to physical and mental education can we reach that high plane of civilization such as has been attained by the people of ancient Hellas,who did this. In them we can see the results of such a course.
Citation: Sweet, K. Elizabeth. Physical training for the mass of students. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Physical Education; Personal Development; Personal Well-Being; Theses